2016
DOI: 10.1002/polb.24063
|View full text |Cite
|
Sign up to set email alerts
|

Functionally integrated liquid crystalline photochromic triple block copolymer with locally light‐ and thermal‐controllable sub‐blocks

Abstract: Photoorientation and reorientation processes induced by illumination of the samples with oppositely directed polarized light and by the thermal treatment were studied for the films of triblock copolymer pAzo 10 -b-pPhM 80 -b-pAzo 10 consisting of a nematic phenyl benzoate central subblock (PhM, DP 5 80) with two terminal smectic azobenzene sub-blocks (Azo, DP 5 10). For amorphized films of triblock copolymer, illumination with polarized light (k 5 546 nm) is shown to be by orientation of only Azo-containing gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In our previous work, we have synthesized LC photosensitive ABA triblock copolymers comprised of azobenzene (Azo) and non‐photosensitive phenyl benzoate (PhM) units . We have also demonstrated that the irradiation of these materials with linearly polarized light and subsequent annealing offer an efficient tool for the selective control over the orientation of Azo and PhM groups …”
mentioning
confidence: 99%
“…In our previous work, we have synthesized LC photosensitive ABA triblock copolymers comprised of azobenzene (Azo) and non‐photosensitive phenyl benzoate (PhM) units . We have also demonstrated that the irradiation of these materials with linearly polarized light and subsequent annealing offer an efficient tool for the selective control over the orientation of Azo and PhM groups …”
mentioning
confidence: 99%
“…Irradiation of Azo polymer films with linearly polarized light is known to induce the orientation of azobenzene groups perpendicularly to the polarization plane leading to dichroism and birefringence 32–34 . As can be seen from Figure 4A, the saturation value of birefringence photoinduсed in the pM2AzoBu film is almost three times higher in comparison with that of the pM10AzoBu film.…”
Section: Resultsmentioning
confidence: 94%
“…[17][18][19][20][21] However, according to our knowledge, there are only a few papers (including our publications) dealing with side-chain photochromic di-and triblock copolymers containing mesogenic groups in each block. [22][23][24][25][26][27] As photochromic fragments in such polymers, azobenzenecontaining groups are most often used. It is well-known, that these groups in azobenzene-containing random comb-shaped copolymers easily undergo the repeated and reversible cyclic processes of trans-cis-trans isomerization under the action of polarized light and this leads to orientation of side groups perpendicular to the electric vector of polarized beam.…”
Section: Doi: 101002/marc202000384mentioning
confidence: 99%
“…to note that LC (mesogenic groups) and photochromic groups can be linked together in each macromolecule of block copolymers by covalent bonds or by using hydrogen bonding. [24][25][26]33] Due to the advancement of polymer synthetic strategies and techniques including controlled living polymerization with facile post-polymerization -functionalization, a variety of block copolymers with precisely controlled molecular weight and welldefined macromolecular architectures can be prepared. [32][33][34] The covalently linked triple block copolymers are now well recognized and used as an innovation strategy of molecular-based functional materials with a new molecular architecture.…”
Section: Photochromic Liquid Crystalline Block Copolymers (Plcbcs) Armentioning
confidence: 99%